2017
DOI: 10.1016/j.jtusci.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to study special kinds of hyperideals in ordered semihyperrings

Abstract: In the present paper, we introduce the notion of k-hyperideals on ordered semihyperrings. Then, we investigate some fundamental properties of k-hyperideals of ordered semihyperrings. Indeed, we define (m, n)-hyperideals and (m, n)-bi-hyperideals in ordered semihyperrings and investigate some of their related properties. Moreover, we introduce and analyze the notion of prime (m, n)-bi-hyperideal of an ordered semihyperring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 16 publications
(15 reference statements)
0
18
0
Order By: Relevance
“…In 2019, Bouaziz and Yaqoob [26] investigated some properties of rough hyperfilters in po-LA-semihypergroups. e notion of (m, n)-hyperideals was introduced in various ordered hyperstructures and had been studied by many authors, for instance, Mahboob et al [27], Omidi and Davvaz [28], and many others.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Bouaziz and Yaqoob [26] investigated some properties of rough hyperfilters in po-LA-semihypergroups. e notion of (m, n)-hyperideals was introduced in various ordered hyperstructures and had been studied by many authors, for instance, Mahboob et al [27], Omidi and Davvaz [28], and many others.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, Tang et al [13] introduced and studied the notion of hyper S-posets over an ordered semihypergroup. Omidi and Davvaz [10] introduced and studied the notion of k-hyperideals in ordered semihyperrings as a generalization of k-hyperideals. In [15], Tang and Xie introduced and studied the notion of weakly prime, quasi-prime, quasi-semiprime and weakly quasi-prime left hyperideals in ordered semihypergroups.…”
Section: Introductionmentioning
confidence: 99%
“…Later on, it was found that the theory also have many applications in both applied and pure sciences. They can be studied in [5], [8], [11], [6] and [13]. The concept of multiplicative hyperring is introduced and studied by R. Rota [12] in 1982.…”
Section: Introductionmentioning
confidence: 99%